Validity And Practicality Of The Internship Program Evaluation Model Mbkm In Politeknik Negeri Padang (Journal of Namibian Studies : History Politics Culture, 2023)
Program evaluation is carried out to determine the achievement of program objectives and provide appropriate recommendations for program improvement. Problems that occur in the student MBKM apprenticeship program have not run optimally in the industry, there is still a gap between the campus and the industry, there has not been clear coordination between apprentice supervisors, industrial instructors and intern students, has not guaranteed student competency achievement, the MBKM apprentice program is still not relevant , there are still various gaps from the findings regarding the MBKM apprentice program implemented in Indonesia. This study aims to develop an evaluation model for the MBKM apprenticeship program. This research produced an evaluation model for the MBKM apprenticeship program, with scheme 1). Preparing, 2). Antecedents, 3). Relevant, 4). Input, 5). Transactiont, 6). Products, 7). Outcome and reflection. The evaluation model for the MBKM apprenticeship program that has been developed is feasible to be used/applied to the evaluation of apprenticeship programs at the Padang State Polytechnic, because the model developed is valid both in the model scheme and apprentice guide for supervisors, apprentice guide for instructors and internship guide for students.